Method for preparing antifouling efficient oil-water separation membrane based on PVDF powder modification and application
By introducing phenolic hydroxyl and hydroxyl groups on PVDF powder, grafted polyquaternary ammonium salts are solved, and the problem of pollution and modification damage of PVDF separation membrane is improved during oil-water separation, and the hydrophilicity and anti-pollution of the membrane are improved. Performance, extends service life and reduces production costs.
Patent Information
- Application Number
- CN202411446747.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2024-12-20
AI Technical Summary
The existing PVDF separation membranes are easily contaminated during oil-water separation, and the membrane surface modification process causes damage to the membrane, affecting its performance and service life.
By soaking the oxidized PVDF powder in a tannin or gallic acid solution, phenolic hydroxyl groups are introduced and reacted with dimethylamine and epoxychlorohydrin to form a grafted polyquaternary ammonium salt, increasing the hydrophilicity of the membrane and anti-pollution of the membrane Performance: Fenton reagent is used to treat PVDF powder in sodium hydroxide solution, introduce hydroxyl groups to form PVDF powder with modification function, and finally form a film in the cast film liquid.
It significantly improves the oil-water separation efficiency and anti-pollution performance of the membrane, reduces damage in the membrane surface modification process, extends the service life of the membrane, and reduces production costs, achieving efficient oil-water separation effect.
Smart Images

Figure CN119158425A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing an antifouling and efficient oil-water separation membrane based on modified PVDF powder and its application, belonging to the field of water treatment science and technology. Background Art
[0002] With the acceleration of industrialization and urbanization, the discharge of oily wastewater has increased dramatically. These wastewaters discharged directly into the environment without treatment will cause serious pollution to the water body. Compared with other water treatment technologies, membrane separation technology has the advantages of high separation efficiency, small footprint, and simple operation. Polyvinylidene fluoride (PVDF) materials are often used in oil-water separation because of their excellent chemical stability, radiation resistance, heat resistance and pollution resistance. However, due to the low surface energy and strong hydrophobicity of PVDF materials, the oil-water separation efficiency is limited. Therefore, hydrophilic modification of PVDF and improving the anti-pollution performance of the membrane have become a hot topic in the field of membrane preparation. Compared with blending and surface coating methods, chemical grafting is more durable in modifying the membrane surface through chemical bonds and has better chemical stability. Summary of the invention
[0003] The purpose of the present invention is to solve the serious membrane fouling problem of existing PVDF separation membranes during oil-water separation, as well as the problem of membrane damage caused by organic reaction processes during membrane surface modification, and to provide a simple, safe and efficient method and application for preparing anti-fouling and efficient oil-water separation membranes based on PVDF powder modification.
[0004] To achieve the above purpose, the technical solution adopted by the present invention is as follows: A method for preparing an antifouling and efficient oil-water separation membrane based on PVDF powder modification comprises the following steps: The oxidized PVDF powder is immersed in a tannic acid or gallic acid solution to obtain a modified powder; The modified powder was reacted with dimethylamine and epichlorohydrin at 55-70°C for 4-6 hours to obtain O-PVDF@TA-MD powder grafted with polyquaternary ammonium salt; The PVDF powder grafted with polyquaternary ammonium salt, a pore-forming agent and an organic solvent are mixed to obtain a film casting solution; The casting solution is subjected to film formation to obtain an antifouling and high-efficiency oil-water separation membrane prepared based on modified PVDF powder.
[0005] A further improvement of the present invention is that the oxidized PVDF powder is prepared by the following process: Alkalizing polyvinylidene fluoride powder in a sodium hydroxide solution to obtain alkaline D-PVDF powder; The FeSO4 and H2O2 solution was added to deionized water to prepare Fenton's reagent; The alkalized D-PVDF powder is added to the Fenton reagent and reacted at 30-60° C. for 10-30 min to obtain oxidized PVDF powder.
[0006] A further improvement of the present invention is that the concentration of the sodium hydroxide solution is 4-8 mol / L and the alkalization time is 1-4 h.
[0007] A further improvement of the present invention is that the Fe in Fenton's reagent 2+ It is 0.02moL / L, and H2O2 is 0.4 moL / L.
[0008] A further improvement of the present invention is that the concentration of the tannic acid or gallic acid solution is 2-8 g / L, and the soaking time is 4-8 h.
[0009] A further improvement of the present invention is that the ratio of O-PVDF@TA powder, dimethylamine and epichlorohydrin is 1~4g:35g:7.83g; The ratio of O-PVDF@GA powder, dimethylamine and epichlorohydrin is: 1~4g:35g:7.83g A further improvement of the present invention is that the pore-forming agent is polyvinyl pyrrolidone or polyethylene glycol, and the organic solvent is N, N -dimethylformamide, N,N -Dimethylacetamide or N -Methylpyrrolidone.
[0010] A further improvement of the present invention is that the ratio of O-PVDF@TA-MD powder, porogen and organic solvent is 1~2g:0.08~0.2g:6~10g.
[0011] An antifouling and high-efficiency oil-water separation membrane prepared based on modified PVDF powder.
[0012] A method for preparing an antifouling and efficient oil-water separation membrane based on PVDF powder modification and its application in oil-water separation.
[0013] Compared with the prior art, the present invention has the following beneficial effects: Tannic acid or gallic acid in the present invention is grafted to the surface of PVDF powder by hydrogen bonding or deposition, and there are a large number of phenolic hydroxyl groups on the surface of tannic acid, which can react with the polyquaternary ammonium salt generated by the reaction of dimethylamine and epichlorohydrin. The oil-water separation efficiency and anti-pollution performance are synergistically improved by using the effects of charge action, II-II stacking, etc. The present invention prepares an efficient oil-water separation membrane by membrane modification technology, directly introduces functional groups on the oxidized PVDF powder for bulk modification, can effectively reduce the damage to the membrane surface during the membrane surface modification process, and simultaneously reduces the transportation production cost, effectively prolongs the service life, and provides technical support for the application of membrane materials in the fields of water treatment, etc. The present invention adopts a simple cationic polymerization reaction, avoids the harm caused by the use of an initiator, and has mild film-making conditions, simple operation, and simple equipment.
[0014] The present invention alkalinizes PVDF powder in a sodium hydroxide solution, which can remove HF from the membrane surface to form unsaturated groups such as double bonds or carbonyl groups without destroying the performance of the PVDF membrane. Then, the OH· free radicals generated by the Fenton reagent attack the unsaturated carbon-carbon double bonds, causing a hydroxylation addition reaction, introducing more hydrophilic groups and increasing the active sites on the PVDF, thereby preparing for the next step of grafting.
[0015] The anti-fouling and high-efficiency oil-water separation membrane prepared based on PVDF powder modification of the present invention is grafted with a large number of hydrophilic groups (hydroxyl, amino, etc.), which can significantly improve the hydrophilicity of the membrane surface and has good anti-pollution ability. Compared with the unmodified ultrafiltration membrane, the oil-water emulsion flux recovery rate is close to about 98% (the unmodified membrane is only about 60%). The application of the high-efficiency oil-water separation membrane prepared based on PVDF powder modification of the present invention in the field of oil-water separation adopts a simple and safe modification method, which effectively solves the serious membrane fouling problem in the oil-water separation process. While ensuring the oil-water separation efficiency of the membrane, it avoids the damage to the membrane surface during the organic reaction process in the film-forming surface modification, improves the anti-pollution and long-term stability of the membrane, and has good application prospects in the field of oil-water separation. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] In order to make the synthesis mechanism, technical scheme and application effect of the present invention clearer, the present invention provides the following drawings: Figure 1 is a scanning electron microscope image of the present invention. Among them, a is a scanning electron microscope image of the original PVDF membrane, b is a scanning electron microscope image of the PVDF membrane after alkalization, c is a scanning electron microscope image of the PVDF membrane treated with Fenton's reagent, and d is a scanning electron microscope image of the PVDF membrane after grafting tannic acid and polyquaternary ammonium salt; Figure 2 is the water contact angle of the O-PVDF@TA-MD membrane of the present invention; Figure 3The pure water flux of the O-PVDF@TA-MD membrane prepared by the present invention; Figure 4 (a) is a comparison chart of diesel emulsion separation performance of the O-PVDF@TA-MD membrane prepared by the present invention and the original PVDF membrane, (b) is a comparison chart of anti-fouling performance of the O-PVDF@TA-MD membrane and the original PVDF membrane; Figure 5 (a) is a comparison chart of the edible oil emulsion separation performance of the O-PVDF@TA-MD membrane prepared by the present invention and the original PVDF membrane, (b) is a comparison chart of the anti-fouling performance of the O-PVDF@TA-MD membrane and the original PVDF membrane; Figure 6 This is a test diagram of the dynamic pollution performance of bovine serum protein solution of the O-PVDF@TA-MD membrane prepared by the present invention and the original PVDF membrane; Figure 7 Flow chart of the preparation of modified PVDF membrane. DETAILED DESCRIPTION
[0017] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present invention are given in the drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly and comprehensively understood.
[0018] As a cationic polymer with a specific chemical structure, polyquaternary ammonium salt can form hydrated ions by hydrogen bonding or ionic bonding with water molecules. It has good water solubility and can quickly separate oil and water.
[0019] Tannic acid (TA) is a natural plant polyphenol with a structure similar to dopamine. It has good substrate adhesion and has been widely used in the field of anti-pollution modification of polymer membranes. Tannic acid combines with the active sites generated on PVDF to introduce a large number of phenolic hydroxyl groups on the PVDF powder. These phenolic hydroxyl groups can further undergo grafting reaction with polyquaternary ammonium salts generated by the reaction of epichlorohydrin and dimethylamine, greatly enhancing the hydrophilicity of the PVDF powder. Directly introducing functional groups on the monomer raw materials for bulk modification can effectively reduce the damage to the membrane surface caused by the organic reaction process in the film-forming surface modification, while reducing the transportation and production costs, effectively extending the service life, and providing technical support for the application of membrane materials in the fields of water treatment. Therefore, in the present invention, tannic acid and polyquaternary ammonium salts are used to perform hydrophilic modification on PVDF.
[0020] See also Figure 7 The present invention provides a method for preparing an antifouling and efficient oil-water separation membrane based on PVDF powder modification, comprising the following steps: (1) alkalizing polyvinylidene fluoride powder in 4-8 mol / L sodium hydroxide solution for 1-4 h to obtain alkalized polyvinylidene fluoride powder, which is recorded as D-PVDF powder; (2) Weigh 0.2782 g of FeSO4 and 2.04 mL of H2O2 solution and dissolve them in 50 mL of deionized water to prepare the required Fenton's reagent. Then add the alkalized D-PVDF powder to the Fenton's reagent and react at 30-60°C for 10-30 min. This is recorded as O-PVDF powder.
[0021] (3) Soak the O-PVDF powder in 2-8 g / L tannic acid or gallic acid solution, react for 4-8 h, wash and dry to obtain O-PVDF@TA powder.
[0022] (4) The O-PVDF@TA powder obtained in step (3) and dimethylamine were placed in a three-necked flask, and then the epichlorohydrin solution was added dropwise, and the mixture was reacted at 55-70°C for 4-6 hours. After being rinsed with deionized water and dried, a PVDF powder grafted with polyquaternary ammonium salt was obtained for standby use, which was named O-PVDF@TA-MD powder. The ratio of O-PVDF@TA powder, dimethylamine and epichlorohydrin was 1-4 g:35 g:7.83 g.
[0023] (5) The PVDF powder grafted with polyquaternary ammonium salt obtained in step (4), a pore-forming agent (PVP or PEG) and an organic solvent ( N,N -dimethylformamide, N, N -dimethylacetamide or N -methyl pyrrolidone to obtain O-PVDF@TA-MD casting solution. N,N -The ratio of dimethylformamide is 1~2g:0.08~0.2g:6~10g.
[0024] (6) The casting solution of step (5) is subjected to a coagulation bath to form a membrane, and is washed with deionized water and ethanol, and dried to obtain an antifouling and efficient oil-water separation membrane based on modified PVDF powder.
[0025] Example 1 4g of polyvinylidene fluoride powder was alkalized in 4mol / L sodium hydroxide solution for 1h. Under the reaction conditions, HF can be removed from the membrane surface to form unsaturated groups such as double bonds or carbonyl groups without destroying the performance of the PVDF membrane. It was repeatedly filtered and rinsed with deionized water and placed in an oven at 60℃ for 12h to obtain D-PVDF powder. Weigh 0.2782g of FeSO4 and 2.04mL of H2O2 solution and dissolve them in 50mL of deionized water to prepare the required Fenton reagent, then add the alkalized D-PVDF powder into the Fenton reagent, react at 30℃ for 30min, filter and rinse repeatedly with deionized water, record it as O-PVDF powder; the OH· free radicals generated by the Fenton reagent attack the unsaturated carbon-carbon double bonds, causing hydroxylation addition reaction, introducing more hydrophilic groups and increasing the active sites on PVDF, preparing for the next grafting step.
[0026] 4g O-PVDF powder was soaked in 2g / L tannic acid solution, reacted for 4h, and then washed and dried to obtain O-PVDF@TA powder. Tannic acid was grafted onto the surface of PVDF powder through hydrogen bonding or deposition. Tannic acid has a large number of phenolic hydroxyl groups on the surface, which can react with polyquaternary ammonium salt.
[0027] 4 g of O-PVDF@TA powder and 34.5 mL of dimethylamine solution were placed in a three-necked flask, and 7.83 mL of epichlorohydrin solution was added to the constant pressure funnel. The mixture was reacted at 60 °C for 6 h and placed in an oven at 60 °C for 12 h to obtain a powder grafted with polyquaternary ammonium salt, which was recorded as O-PVDF@TA-MD powder.
[0028] 1g O-PVDF@TA-MD powder was mixed with 0.1g porogen PVP and 8mL N,N- After dimethylformamide was mixed, the mixture was reacted at 60°C for 6 hours and allowed to stand for 12 hours to obtain a uniform, bubble-free casting solution.
[0029] The coagulation bath used in the present invention is a deionized water coagulation bath. The casting solution is poured onto a clean glass plate, and a film with a thickness of 200 μm is coated with a coating rod. After standing for 10 seconds, the film is immersed in deionized water to undergo phase transformation into a film. After the PVDF film automatically falls off the glass plate, the film is taken out and immersed in clean deionized water for 24 hours to remove excess solvent and porogen in the film. The prepared PVDF ultrafiltration membrane is immersed in anhydrous ethanol and water successively to remove organic matter and impurities on the membrane surface, and then dried to obtain an antifouling and efficient oil-water separation membrane prepared based on PVDF powder modification, and the average pore size of the separation membrane is 0.0559 μm, which is for standby use.
[0030] See also Figure 1In (a) and (b), the above-mentioned PVDF powder, D-PVDF powder, O-PVDF powder, and O-PVDF@TA-MD powder were prepared into membranes using the existing method, marked as a, b, c, and d, respectively. The surface microstructures were observed by scanning electron microscopy (SEM). Compared with the original PVDF membrane a, the modified PVDF ultrafiltration membranes b, c, and d had more micropores on their surfaces, and the pore sizes became larger and the distribution became more uniform. The larger pore size means that the modified membrane has better water flux performance. After soaking in tannic acid and grafted polyquaternary ammonium salt, the surface pore size of membrane d was reduced, and the reduced pore size was beneficial to improving the retention performance of the membrane.
[0031] Pure water flux test: Fix the sample membrane in the center of two glass containers, turn on the circulating vacuum pump to exhaust the air in the filter bottle, wait until the vacuum value stabilizes at 0.06MPa, pour in 30 mL of ultrapure water, and use a stopwatch to record the time it takes for the ultrapure water to pass through the membrane. Figure 3 As shown, the pure water flux of the modified membrane was significantly higher than that of the unmodified PVDF membrane.
[0032] In the formula, J W Represents water flux, in units of (L∙m -2 ∙h -1 ), V w represents the volume of filtered water, A represents the effective test area, and t is the filtering time.
[0033] Contact angle test: Test the water contact angle (WCA) and underwater diesel contact angle (UOCA) of the original PVDF membrane and the modified PVDF membrane in air. Figure 2 As shown, the contact angle of the original membrane is 81.0°, and the contact angle of the modified PVDF membrane is 44.0°, which proves that the modified membrane has good hydrophilicity. The underwater oil contact angle of the original membrane is measured to be 109.1°, and the underwater oil contact angle of the modified membrane is 137.3°, indicating that the modified membrane has a good underwater oil contact angle. Oil-water emulsion separation performance test: After fixing the membrane in the vacuum filtration device, turn on the circulating vacuum water pump, wait until the vacuum degree is stable at 0.06 MPa, pour in 50 mL of the prepared oil-water emulsion, and use a stopwatch to record the time it takes for the emulsion to pass through the membrane. The emulsion flux is calculated according to the above formula. Then collect the oily wastewater stock solution and filtrate, and use the total organic carbon analyzer to determine the organic matter content in it to calculate the oil retention rate ( R ), the calculation formula is as follows:
[0034] In the formula, C pIndicates the oil content in the filtrate, C p Indicates the oil content in the feed liquid.
[0035] Water flux recovery rate ( FRR ) Test: Flux recovery rate is the most common indicator used to evaluate dynamic membrane fouling. The higher the flux recovery rate, the better the anti-fouling performance. Fix the membrane sample to be tested in a vacuum filtration device, turn on the circulating vacuum water pump to extract the air in the bottle, filter pure water for 30 minutes, turn on the circulating vacuum water pump to exhaust the air in the filtration bottle, and after the vacuum value stabilizes at 0.06MPa, pour in 30 mL of ultrapure water to obtain a stable water flux. J w; Then, the oil-water emulsion or BSA solution was used instead of pure water and tested under the same conditions to obtain a stable filtrate flux. J After that, the membrane sample was repeatedly rinsed with pure water, and the pure water was filtered for 30 minutes after the rinsing to obtain a stable second pure water flux. J R。
[0036] FRR =
[0037] In the formula, J w (L∙m -2 ∙h -1 )、 J R (L∙m -2 ∙h -1 ) are the pure water fluxes for the first and second times respectively.
[0038] like Figure 4 In (a), (b) and Figure 5 As shown in (a) and (b), by comparing the emulsion separation tests of the PVDF membranes before and after modification, it can be seen that the modified PVDF membrane (O-PVDF@TA-MD) is significantly higher than the original PVDF membrane in filtrate flux, retention rate and flux recovery rate due to the introduction of a large number of hydrophilic groups.
[0039] Protein dynamic contamination test: 1g / L bovine serum albumin (BSA) solution was prepared to simulate protein wastewater, and the membrane's anti-protein contamination performance was evaluated. The sample membrane to be tested was fixed in a vacuum filtration device, and the circulating vacuum water pump was turned on to extract the air in the bottle. After the vacuum value stabilized, 30 mL of ultrapure water was poured in, and the time was recorded to calculate the flux. Jw; then pour in 50 mL of 1g / L BSA solution, wait for the BSA solution to pass through completely, take out the membrane, wash it with anhydrous ethanol and ultrapure water, filter 30 mL of ultrapure water again and record the time, and calculate the flux at this time J R The anti-protein pollution effect was calculated according to Example 4. Figure 6 As shown in the figure, the water flux of the original PVDF membrane decreased significantly after filtering the bovine serum albumin solution, and the water flux recovery rate of the modified membrane was significantly higher than that of the original PVDF membrane, indicating that the modified membrane is not easily contaminated, easy to clean, and has good anti-fouling performance.
[0040] Example 2 (1) 4 g of polyvinylidene fluoride powder was alkalized in 8 mol / L sodium hydroxide solution for 1 h to obtain alkalized D-PVDF powder; (2) The alkalized PVDF powder is placed in Fe 2+ The reaction was carried out in a Fenton reagent with a concentration of 0.02 mol / L and 0.4 mol / L H2O2 at 30°C for 30 min to obtain oxidized PVDF powder, which was recorded as O-PVDF powder.
[0041] (3) 4 g of O-PVDF powder was soaked in 5 mg / mL tannic acid solution and reacted for 6 h. The mixture was then washed and dried to obtain O-PVDF@TA powder.
[0042] (4) 2 g of the O-PVDF@TA powder obtained in step (3) and 1.5 mol of dimethylamine were placed in a three-necked flask, and 1.1 mol of epichlorohydrin solution was added dropwise. The mixture was reacted at 55 °C for 6 h. After being rinsed with deionized water and dried, a PVDF powder grafted with polyquaternary ammonium salt was obtained for standby use and named O-PVDF@TA-MD.
[0043] (5) 1 g of the polyquaternary ammonium salt-grafted PVDF powder obtained in step (4), 0.08 g of a pore-forming agent (PVP) and 6 g of an organic solvent (N,N-dimethylformamide) were mixed to obtain an O-PVDF@TA-MD casting solution.
[0044] (6) The coagulation bath used in the present invention is a deionized water coagulation bath. The casting solution is poured onto a clean glass plate, and a film with a thickness of 200 μm is coated with a coating rod. After standing for 10 seconds, the film is immersed in deionized water to undergo phase transformation into a film. After the PVDF film automatically falls off the glass plate, it is taken out and immersed in clean deionized water for 24 hours to remove excess solvent and porogen in the film. The prepared PVDF ultrafiltration membrane is immersed in anhydrous ethanol and water successively to remove organic matter and impurities on the membrane surface, and then dried to obtain an antifouling and efficient oil-water separation membrane based on PVDF powder modification.
[0045] Example 3 (1) 4 g of polyvinylidene fluoride powder was alkalized in 7 mol / L sodium hydroxide solution for 3 h to obtain alkalized D-PVDF powder; (2) The alkalized PVDF powder is placed in Fe 2+ The reaction was carried out in a Fenton reagent containing 0.02 mol / L H2O2 and 0.4 mol / L H2O2 at 60°C for 10 min to obtain oxidized PVDF powder, which was recorded as O-PVDF powder.
[0046] (3) 4 g of O-PVDF powder was soaked in 8 mg / mL gallic acid solution and reacted for 8 h. The solution was then washed and dried to obtain O-PVDF@GA powder.
[0047] (4) 4 g of the O-PVDF@GA powder obtained in step (3) and 2 mol of dimethylamine were placed in a three-necked flask, and 1.2 mol of epichlorohydrin solution was added dropwise. The mixture was reacted at 70° C. for 4 h. After being rinsed with deionized water and dried, a PVDF powder grafted with polyquaternary ammonium salt was obtained and was set aside and named O-PVDF@GA-MD.
[0048] (5) 2 g of the polyquaternary ammonium salt-grafted PVDF powder obtained in step (4), 0.2 g of a pore-forming agent (PEG), and 10 mL of an organic solvent (N,N-dimethylacetamide (DMAc)) were mixed to obtain an O-PVDF@GA-MD casting solution.
[0049] (6) The coagulation bath used in the present invention is a deionized water coagulation bath. The casting solution is poured onto a clean glass plate, and a film with a thickness of 200 μm is coated with a coating rod. After standing for 10 seconds, the film is immersed in deionized water to undergo phase transformation into a film. After the PVDF film automatically falls off the glass plate, it is taken out and immersed in clean deionized water for 24 hours to remove excess solvent and porogen in the film. The prepared PVDF ultrafiltration membrane is immersed in anhydrous ethanol and water successively to remove organic matter and impurities on the membrane surface, and then dried to obtain an antifouling and efficient oil-water separation membrane based on PVDF powder modification.
[0050] Example 4 (1) 4 g of polyvinylidene fluoride powder was alkalized in a 6 mol / L sodium hydroxide solution for 4 h to obtain alkalized D-PVDF powder; (2) The alkalized PVDF powder is placed in Fe 2+ The reaction was carried out in a Fenton reagent containing 0.02 mol / L H2O2 and 0.4 mol / L H2O2 at 45°C for 20 min to obtain oxidized PVDF powder, which was recorded as O-PVDF powder.
[0051] (3) 4 g of O-PVDF powder was soaked in 2 mg / mL gallic acid solution and reacted for 8 h. The solution was then washed and dried to obtain O-PVDF@TA powder.
[0052] (4) 1 g of the O-PVDF@TA powder obtained in step (3) and 1 mol of dimethylamine were placed in a three-necked flask, and 1 mol of epichlorohydrin was added dropwise. The mixture was reacted at 60°C for 5 h. After being rinsed with deionized water and dried, a PVDF powder grafted with polyquaternary ammonium salt was obtained and was set aside for use. It was named O-PVDF@TA-MD.
[0053] (5) 1.5 g of the PVDF powder grafted with polyquaternium salt obtained in step (4), 0.1 g of a pore-forming agent (PVP) and 8 mL of an organic solvent were mixed. N -methyl pyrrolidone (NMP) to obtain O-PVDF@TA-MD casting solution.
[0054] (6) The coagulation bath used in the present invention is a deionized water coagulation bath. The casting liquid is poured onto a clean glass plate, and a film with a thickness of 200 µm is coated with a coating rod. After standing for 10 seconds, the film is immersed in deionized water to undergo phase transformation into a film. After the PVDF film automatically falls off the glass plate, it is taken out and immersed in clean deionized water for 24 hours to remove excess solvent and porogen in the film. The prepared PVDF ultrafiltration membrane is immersed in anhydrous ethanol and water successively to remove organic matter and impurities on the membrane surface, and then dried to obtain an antifouling and efficient oil-water separation membrane prepared based on PVDF powder modification. The present invention utilizes alkaline solution to treat PVDF powder to generate double bonds, the alkalized powder is oxidized by Fenton reagent to generate hydroxyl groups, immersed in tannic acid solution, a large number of phenolic hydroxyl groups are generated on the surface of PVDF by hydrogen bonds, and then grafted with polyquaternary ammonium salt obtained by reaction with epichlorohydrin and dimethylamine, and finally dissolved in N, N-dimethylformamide solvent to obtain uniform casting liquid, and a membrane is obtained by phase inversion method. The membrane has good antifouling function, can effectively alleviate the serious membrane pollution problem in the oil-water separation process, has good membrane hydrophilicity, fast oil-water separation effect, mild reaction conditions, and simple operation. The hydrophilic groups are introduced directly on the powder, which effectively reduces the damage to the membrane surface during the modification process, reduces the transportation and production costs, and effectively prolongs the service life.
[0055] The above description is only for the best embodiment of the present invention, but it should not be understood as limiting the claims. The present invention is not limited to the above embodiments, and its specific structure is allowed to be changed. However, all changes made within the protection scope of the independent claims of the present invention are within the protection scope of the present invention.
[0056] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
Claims
1. A method for preparing an antifouling and efficient oil-water separation membrane based on PVDF powder modification, It is characterized in that The following steps are involved: The oxidized PVDF powder is immersed in a tannic acid or gallic acid solution to obtain a modified powder; The modified powder was reacted with dimethylamine and epichlorohydrin at 55-70°C for 4-6 hours to obtain O-PVDF@TA-MD powder grafted with polyquaternary ammonium salt; The PVDF powder grafted with polyquaternary ammonium salt, a pore-forming agent and an organic solvent are mixed to obtain a film casting solution; The casting solution is subjected to film formation to obtain an antifouling and high-efficiency oil-water separation membrane prepared based on modified PVDF powder.
2. The method for preparing an antifouling and efficient oil-water separation membrane based on modified PVDF powder according to claim 1, It is characterized in that Oxidized PVDF powder is prepared by the following process: Alkalizing polyvinylidene fluoride powder in a sodium hydroxide solution to obtain alkaline D-PVDF powder; Will FeSO 4 With H 2 O 2 The solution was added to deionized water to prepare Fenton's reagent; The alkalized D-PVDF powder is added to the Fenton reagent and reacted at 30-60° C. for 10-30 min to obtain oxidized PVDF powder.
3. The method for preparing an antifouling and efficient oil-water separation membrane based on PVDF powder modification according to claim 2, It is characterized in that The concentration of sodium hydroxide solution is 4~8mol / L, and the alkalization time is 1~4h.
4. The method for preparing an antifouling and efficient oil-water separation membrane based on PVDF powder modification according to claim 2, It is characterized in that Fe in Fenton's reagent 2+ 0.02moL / L, H 2 O 2 It is 0.4 mol / L.
5. The method for preparing an antifouling and efficient oil-water separation membrane based on PVDF powder modification according to claim 1, It is characterized in that The concentration of tannic acid or gallic acid solution is 2~8g / L, and the soaking time is 4~8h.
6. The method for preparing an antifouling and efficient oil-water separation membrane based on PVDF powder modification according to claim 1, It is characterized in that The ratio of O-PVDF@TA powder, dimethylamine and epichlorohydrin is 1~4g:35g:7.83g; The ratio of O-PVDF@GA powder, dimethylamine and epichlorohydrin is 1~4g:35g:7.83g.
7. The method for preparing an antifouling and efficient oil-water separation membrane based on modified PVDF powder according to claim 1, It is characterized in that The pore-forming agent is polyvinyl pyrrolidone or polyethylene glycol, and the organic solvent is N,N -dimethylformamide, N,N -Dimethylacetamide or N -Methylpyrrolidone.
8. The method for preparing an antifouling and efficient oil-water separation membrane based on PVDF powder modification according to claim 1, It is characterized in that The ratio of O-PVDF@TA-MD powder, porogen and organic solvent is 1~2g:0.08~0.2g:6~10g.
9. An antifouling and high-efficiency oil-water separation membrane prepared by modifying PVDF powder according to the method of any one of claims 1 to 8.
10. Use of an antifouling and efficient oil-water separation membrane prepared by modifying PVDF powder according to the method of any one of claims 1 to 8 in oil-water separation.
